Essays on Chinese cross-border mergers and acquisitions - Hu, Shuang (2021)
The introduction and conclusion notwithstanding, this thesis contains four essays on the theme of Chinese cross-border mergers and acquisitions (CBMAs). As essays they can be viewed ‘stand-alone’, with their own ‘separate’ contributions adding to the body of knowledge on the thesis’s theme. Yet, the first two essays can be seen as providing a foundation for the ‘empirical’ essays, in that they contribute to identify research gaps and new directions (though using different ‘approaches’). The next two empirical essays address specific unanswered research questions, some identified in the aforementioned essays . In Chapter 1 (the introduction), we describe the general background of Chinese CBMAs and research motivations for the thesis. Then we illustrate the ‘specific’ research objectives and questions addressed in the four essays and outline the thesis structure. Chapter 2 or Essay 1 adopts a ‘stylised facts’ approach to document the recent trends/patterns of Chinese CBMAs, whether pertaining to the deals value or frequency, spatial and industrial distribution, and ownership stakes. This essay contends that such a ‘simple’ fact-finding exercise that eschews any theorising and empirical causal examination can be highly insightful and provide guidance for new directions in research. The exercise documents several ‘new’ interesting facts about Chinese MNEs’ international acquisitions, some distinct from what is currently seen as received wisdom. It finds that both the value and frequency of Chinese CBMAs deals are in the process of ‘catching up’ to greenfield investments and identifies a regional orientation to Chinese CBMAs, whilst documenting the latter’s global reach as well (when we analyse both value and frequency of deals). Chinese MNEs are possibly transforming their value chain from backward to forward integration, with industrial upgrading as aim and a preference for more radical acquisition approaches. Several research questions directed for future research – to theorise and empirically examine the antecedents of the phenomenon – are outlined. Chapter 3 or Essay 2 provides a critical review and then proposes an ‘integrative’ conceptual framework to better organise our thinking on Chinese CBMAs. It explicitly articulates limitations of extant research and highlight aspects for future directions to investigate Chinese CBMAs based on a literature review. Two schools of thoughts – one management-oriented and one finance-oriented – highlight distinctive views on the antecedents of Chinese CBMA decision. Moreover, we find that variations on post-CBMA firm performance can be influenced by both CBMA motivation and integration process. It is this chapter’s contention that M&A decision, integration and performance could be studied together as most mergers and acquisitions are made of these three elements that interact with each other, while simultaneously acting as part of a whole system. The chapter eventually proposes a conceptual framework dubbed the ‘decision-integration-performance’ framework of CBMAs. This provides a means to study integration and performance together, which so far has been studied separately, and consider antecedents or motives behind acquisition decision with both merger integration and post-merger performance. From a practical standpoint it connects the antecedents of ‘why mergers fail’ (e.g. overconfidence/hubris) with the integration process which could provide a better understanding behind post-merger under-performance, when managerial motives are factored in. From an empirical methodological viewpoint (e.g. Heckman sample selection bias), it cautions us about ignoring M&A decision when studying post-merger performance (often seen in extant literature) .We view this allowing a closer connection between theoretical framework and empirical framework used to study theoretical predictions. Chapter 4 or Essay 3 empirically tests the contribution of the country-specific advantages (CSAs) and firm-specific advantages (FSAs), as sources of competitive advantages, to productivity variation of Chinese MNEs subsequent to CBMAs, while controlling for ex-ante CBMA FSAs. It uses a paired sample of CBMA firms by propensity-score matching during the period 2007–2017. The findings indicate that Chinese MNEs experienced lower productivity after CBMAs, thus indicative of a failure to generate FSAs or CSAs from CBMAs. It also demonstrates that post-CBMA productivity varies according to host country factors and firm heterogeneity. Non-state owned enterprises with strong absorptive capacity obtain higher productivity when investing in resource-abundant countries. The chapter contributes theoretically to our understanding of the sources of competitive advantages ex post (subsequent to EMNEs CBMAs). It investigates whether ex post competitive advantages accrue to EMNEs through CBMAs and how firm and host country heterogeneity moderates CBMA’s effect on CSAs and FSAs. Chapter 5 or Essay 4 tests whether Africa offers a different proposition to Chinese business interests than when investing in non-African developing economies. It takes a “comparative” institution-based view treating factors that determine Chinese CBMA as comparatively different for Africa to the rest of the developing world. It finds that only natural resources and market size have a distinctive effect, with Chinese investors being more attracted to African natural resources than the African market. The drive for natural resources provides impetus for Chinese MNEs to choose CBMAs over greenfield investments, and through majority ownership to exercise control. The chapter contributes theoretically to the comparative perspective of the institutional-based view by offering a novel understanding of whether and how Africa acting as a particular kind of institutional configuration influences Chinese CBMAs distinctively from other developing regions’ national institutions. Chapter 6 (the conclusion) summarises the main findings and implications of the thesis and provides some ‘general’ implications for the thesis as a ‘whole’ and a short discussion for future research directions.